ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA MANAJERIAL - Taufik Hidayat (Department of Accounting-Faculty of Economic and Business (FEB), 2014)
The purpose of this study is to examine the budget planning system,participation in drafting the budget, budget scheduling and budget goal clarity to managerialperformance, as well as to search an internal control, and it may modernize the influence ofbudget planning system, participation in drafting the budgets, budget scheduling and budgetgoal clarity to managerial performance. This study is recognized as a causal research, and thelocation of study is Islamic state university Jakarta taking a sample of 69 respondents fromthe faculty and the rector. The test tool on hypothesis one is with t test used in evaluating thehypothesis partially, and f test is used to search its influence simultaneously, while forsearching to hypothesis two is to see the influence of moderating variable is as adopted toanalyze the difference absolutely. Refers to the result of analysis is concluded that it partialsystem of budget planning, budget participation and budget goal clarity significant effect tomanagerial performance, while the budget schedule accuracy is not having an effect onmanagerial performance. It is also found that the internal control may not leadmodernization any influence of the budget planning system, participation in drafting thebudgets, budget scheduling and budget goal clarity to managerial performance.DOI: 10.15408/akt.v7i1.2646